A Study of Doppler velocimetry in pre-eclampsia patients, and their perinatal outcome - Khatri, Rahul; Jain, Bhoomika; Mhapankar, Sabrina; Kumar, Sushil (Clinical Journal of Obstetrics and Gynecology, 2021)
Pre eclampsia and IUGR are important causes of maternal and perinatal morbidity and mortality. Pre eclampsia is a multisystem disorder, in normal pregnancies trophoblastic invasion transforms high resistance spiral arteries into low impedance uteroplacental circulation. This uteroplacental circulation remains incomplete in pre eclampsia and IUGR. This study is to correlate the Doppler Findings with the Fetal Outcome in pre eclampsia patiens, and helps decide appropriate time for delivery with least perinatal morbidity.